2016
DOI: 10.1021/acs.iecr.5b04152
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Activity Coefficient of Thiophene at Infinite Dilution in Ionic Liquids and their Modeling Using COSMO-RS

Abstract: Ionic liquids (ILs) gained a lot of attention, from both academe and industry, as alternative liquids for different types of applications. Chemical and physical characteristics can be designed with the large availability of cation and anions. Experimental measurement of all these systems is not practically feasible, hence requiring the use of a computational predictive model study. This work evaluates the prediction of the activity coefficient (γ s ∞) at infinite dilution in several classes of ILs using the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…20 It has also attracted a significant amount of attention in terms of ILs, as it integrates the dominant interaction forces of H-bonds, misfits and van der Waals in ILs systems. [21][22] Many results on the prediction of polymer properties in ILs have been reported, and it is obvious that calculating the activity coefficients, 23 solubility coefficients 1,24 and excess enthalpy 25 of polymer in ILs is an effective way of evaluating the dissolution ability of the ILs. Casas et al, 26 for instance, found that the solubility of cellulose and lignin could be accurately predicted by using activity coefficients and excess enthalpy via COSMO-RS.…”
Section: Introductionmentioning
confidence: 99%
“…20 It has also attracted a significant amount of attention in terms of ILs, as it integrates the dominant interaction forces of H-bonds, misfits and van der Waals in ILs systems. [21][22] Many results on the prediction of polymer properties in ILs have been reported, and it is obvious that calculating the activity coefficients, 23 solubility coefficients 1,24 and excess enthalpy 25 of polymer in ILs is an effective way of evaluating the dissolution ability of the ILs. Casas et al, 26 for instance, found that the solubility of cellulose and lignin could be accurately predicted by using activity coefficients and excess enthalpy via COSMO-RS.…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in Table , the MAPE between experimental and UNIFAC‐IL calculated γ ∞ of thiophene for the 405 data points is only 4.42%. In comparison, the MAPE between experimental and COSMO‐RS predicted γ ∞ of thiophene in 52 ILs (325 data points) is 24.10% . Similarly, the corresponding MAPEs in the cases of aromatics, n ‐alkanes, and cycloalkanes are 10.05%, 26.82%, and 32.28%, respectively, which are also much smaller than the ones predicted from COSMO‐RS .…”
Section: Extension Of the Unifac‐il Model To The Eds Systemmentioning
confidence: 84%
“…These models include predictive quantitative structure–activity relationship (QSAR) models, molecular docking, structure–activity relationship (SAR) systems, read‐across models, physiology‐based pharmacokinetic models, and quantitative toxicity–toxicity relationship (QTTR) models . In addition to toxicity predictions, these models have been successful in forecasting various physicochemical properties of ILs, such as melting points, surface tensions, infinite dilution activity coefficients, viscosities, conductivities, solubilities, glass transition temperatures, and decomposition temperatures …”
Section: Computational Prediction Of the Toxicity Of Ionic Liquidsmentioning
confidence: 99%
“…These models include predictive quantitative structure-activity relationship (QSAR) models, [42][43][44][45] molecular docking, [46] structure-activity relationship (SAR) systems, [47] read-across models, [48][49][50] physiology-based pharmacokinetic models, [51,52] and quantitative toxicity-toxicity relationship (QTTR) models. [53] In addition to toxicity predictions, these models have been successful in forecasting various physicochemical properties of ILs, such as melting points, [54,55] surface tensions, [56,57] infinite dilution activity coefficients, [58][59][60] viscosities, [61,62] conductivities, [63,64] solubilities, [65,66] glass transition temperatures, [64] and decomposition temperatures. [67] Determining the relationship between toxicity and structural features is one of the most basic processes of a model and this is made possible through computational chemistry.…”
Section: Computational Prediction Of the Toxicity Of Ionic Liquidsmentioning
confidence: 99%